Production Of Polypropylene Bags (Texas Journal of Engineering and Technology, 2022)
In this article is given the manufacture of polypropylene bags, in particular development technology production of bags and bag fabrics, technological processes for treatment and preparation of raw materials to weaving, chosen and proved equipments and especially for making bags and bag fabrics. cost performance equipments are also given for the production of polypropylene bags in USD.